Everolimus plus bevacizumab is an effective first‐line treatment for patients with advanced papillary variant renal cell carcinoma: Final results from a phase II trial. Issue 24 (25th September 2020) - Feldman, Darren R.; Ged, Yasser; Lee, Chung‐Han; Knezevic, Andrea; Molina, Ana M.; Chen, Ying‐Bei; Chaim, Joshua; Coskey, Devyn T.; Murray, Samuel; Tickoo, Satish K.; Reuter, Victor E.; Patil, Sujata; et al.
Abstract : Background: We previously reported on a phase 2 study of everolimus plus bevacizumab across various nonclear cell renal cell carcinoma (nccRCC) histologies and observed encouraging activity among patients with papillary RCC (pRCC) and unclassified RCC (uRCC) with a major papillary component. We subsequently expanded the study to enroll additional patients with pRCC variants. Methods: Everolimus plus bevacizumab was administered at standard doses until disease progression or intolerance to therapy. The primary endpoint was the 6‐month progression‐free survival (PFS) rate; secondary endpoints included objective response rate (ORR), progression‐free survival (PFS), overall survival (OS), and safety. Correlative analyses included next‐generation sequencing (NGS) from tumor and germline across >341 genes of interest. Results: In addition to 19 patients with pRCC variants in the original cohort, 20 patients with similar features were enrolled on the expansion cohort (uRCC with papillary features [n = 24], pRCC [n = 14], and translocation‐associated RCC with papillary features [n = 1]). Among 37 evaluable patients, the 6‐month PFS rate was 78%, the median PFS was 13.7 months (95% CI, 10.8‐16.4 months), and the ORR was 35%. With a median follow‐up of 17.6 months, the median OS was 33.9 months (95% CI, 23.3‐71.9). Tolerance was consistent with prior reports for everolimus plus bevacizumab. NGS results (n = 33) identified responses in patients with a wide spectrum of genomic alterations, including ARID1A, FH, and MET mutations. Conclusion: The expansion cohort results confirm robust activity of everolimus plus bevacizumab in metastatic pRCC variants, supporting this regimen as a standard option for this patient population. Abstract : The combination of everolimus plus bevacizumab demonstrates robust activity in patients who have papillary variant renal cell carcinoma. These data support this regimen as a standard first‐line treatment option in this patient population.